Search
Ask a question
0

-3 (5 – 2y) =

how do i go about solving this equation, step by step ?

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Miguel M. | Math and Science Tutor with 30+ Years Teaching ExperienceMath and Science Tutor with 30+ Years Te...
4.9 4.9 (93 lesson ratings) (93)
0
I assume there is no answer to the right of the = sign. So this is a simplification problem. Get rid of the parentheses by multiplying everything inside the parentheses by -3. Remember that - x - = +:
-3 x 5 - (-3)x 2y = -15 + 6 y.